2017
DOI: 10.1107/s2052520617010769
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional structural variation in the cyanotrichite family of merotypes: camerolaite-3b-F\bar 1

Abstract: A new superstructure of the mineral camerolaite, CuAl(OH)(HO)[Sb(OH)](SO), has been refined in space group P\bar 1 with unit-cell parameters a = 7.7660 (16), b = 8.759 (4), c = 11.306 (2) Å, α = 108.67 (4), β = 83.41 (3), γ = 126.64 (2)°, V = 581.6 (3) Å and Z = 1, with R = 0.0951 (all data). This is the first refined example of a cyanotrichite-group mineral in which long-range order of interlayer anions produces a superstructure along b, although diffuse scattering has previously been reported that correspond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The end of the wall includes a large cavity where 5 out of the 14 new species known at Cap Garonne have been found: geminite (Sarp and Perroud, 1990), guarinoite (Sarp, 1993), mahnertite (Sarp, 1996), pushcharovskite (Sarp and Sanz-Gysler, 1997) and thérèsemagnanite (Sarp, 1993). This specimen was collected as part of the systematic study of the mine mineralogy by Association des Amis de la Mine de Cap Garonne (Favreau and Galea-Clolus, 2014; Mills et al ., 2014, 2015, 2017, 2018; Plášil et al ., 2018).…”
Section: Occurrencementioning
confidence: 99%
“…The end of the wall includes a large cavity where 5 out of the 14 new species known at Cap Garonne have been found: geminite (Sarp and Perroud, 1990), guarinoite (Sarp, 1993), mahnertite (Sarp, 1996), pushcharovskite (Sarp and Sanz-Gysler, 1997) and thérèsemagnanite (Sarp, 1993). This specimen was collected as part of the systematic study of the mine mineralogy by Association des Amis de la Mine de Cap Garonne (Favreau and Galea-Clolus, 2014; Mills et al ., 2014, 2015, 2017, 2018; Plášil et al ., 2018).…”
Section: Occurrencementioning
confidence: 99%
“…In the course of our ongoing study of the structure and chemistry of minerals from the Cap Garonne copper mine (Favreau and Galea-Clolus, 2014; Grey et al , 2014; Mills et al , 2014, 2015, 2017, 2018, 2019; Plášil et al , 2018), one of us (G.F.) located fibrous coatings of a white mineral for which energy-dispersive X-ray analysis gave the same composition as reported for bulachite (Walenta, 1983). A PXRD pattern for the mineral had a number of sharp peaks in common with those for bulachite, but the pattern did not contain the strongest bulachite peak at 7.78 Å and it contained several broad peaks not present in the Walenta (1983) pattern, with the strongest peak being at d ≈ 10 Å. Electron diffraction (ED) patterns obtained on individual fibres enabled the PXRD pattern to be indexed with a unit cell having the same b and c parameters as bulachite, but with a increased to ~19.9 Å. Thermo-crystallographic studies on the Cap Garonne specimen (Grey et al , 2020b) showed that the PXRD pattern started transforming to that for bulachite at ~50°C and the transformation was complete above 75°C.…”
Section: Introductionmentioning
confidence: 99%
“…bariopharmacoalumite- Q 2 a 2 b 2 c, Grey et al , 2014) and exceptionally large crystals have been used to help solve the structures of minerals in combination with high-brilliance synchrotron radiation (e.g. cyanotrichite, Mills et al ., 2015; camerolaite, Mills et al ., 2017). Exceptional crystals of the hydrated copper aluminium arsenate ceruleite have been discovered at the mine and, in combination with synchrotron radiation, have been used to elucidate the structure of the mineral first described by Dufet in 1900.…”
Section: Introductionmentioning
confidence: 99%